Epstein-Barr virus, vitamin D and the immune response: connections with consequences for multiple sclerosis - Rasheed, Atia; Khan, Gulfaraz (Frontiers in Immunology, 2024)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) with no definitive trigger. However, epidemiological studies indicate that environmental factors, such as infection with Epstein-Barr virus (EBV) and low vitamin D (Vit D) levels in genetically predisposed individuals, are important risk factors. One leading proposal is that EBV triggers MS via mechanisms such as molecular mimicry, where activated autoreactive B and T lymphocytes mistakenly target self-antigens. In line with other risk factors, low serum Vit D level, genetic polymorphism of Vit D receptor, and higher incidence of MS in countries in the northern hemisphere, suggest that Vit D also plays a role in MS pathology. Vitamin D, known for its neuroprotective and immunomodulatory effects, helps maintain a balance between pro-inflammatory and anti-inflammatory immune cells. Studies and ongoing clinical trials indicate that hypovitaminosis D is associated with an increased risk of MS, and Vit D supplement can help to reduce the disease severity. Moreover, hypovitaminosis D has also been associated with a dysregulated immune system and an increased risk of developing MS. This review explores how these three well-recognized risk factors - EBV infection, hypovitaminosis D, and dysregulated immune system - interact in the pathogenesis of MS. Understanding these interactions and their consequences could provide new insights into novel therapeutic approaches for treating this devastating disease.